A Review of Limitations of Wind Synthetic Inertia Methods - Chavez-Orostica, H; Fuentes-Parra, C; Riquelme-Vera, E (Institute of Electrical and Electronics Engineers Inc., 2020)
The rise of wind power penetration ijn power system has led to a deterioration of frequency response and a reduction of inertia levels. The proposals of methodologies for wind turbines to alleviate the effect of wind integration by providing frequency response are numerous, but most of these proposals consider simplifying assumptions that prevent their efficient or optimal performance. In this work, various synthetic inertia techniques are reviewed, establishing their limitations in terms of modeling to achieve optimality and representativeness of the model. The analysis establishes that the treatment of non-linearities and the lack of an objective function are the main limitations. © 2020 IEEE.